Exceptional patterns of object marking in Bantu - Michael R. Marlo (LibraryPress@UF, 2014)
This article discusses three main phenomena in the morpho-syntax and morpho-phonology of Bantu languages in which the 1SG object prefix (OP) and/or the reflexive, display anomalous properties compared to other OPs. (i) The 1SG OP and the reflexive commonly have unique combinatorial properties with additional OPs. (ii) The 1SG OP (or, rarely, the reflexive as well) triggers different patterns of final vowel (FV) allo-morphy in the imperative. (iii) The 1SG OP but usually not the reflexive behave different-ly in reduplication. Each of these phenomena is the subject of a micro-typological survey within Bantu, the results of which support the conclusion that morpho-syntactic and mor-pho-phonological factors are responsible for the full range of anomalous patterns of the 1SG OP and reflexive across Bantu. The exceptional abilities of the 1SG OP and reflexive OP to combine with an extra OP and to trigger a different pattern of FV allomorphy in the imperative are the result of a distinct, lower structural position of the 1SG and reflex-ive prefixes compared to other OPs, but the overcopying of the 1SG OP in reduplication has a phonological basis.